Analysis of cryptocurrency verification challenges faced by the South African Revenue Service and tax authorities in other BRICS countries and whether SARS’ powers to gather information relating to cryptocurrency transactions are on par with those of other BRICS countries - Scheepers, Jill (Department of Finance and Tax, 2020)
The main objective of this study was to identify the potential difficulties that the verification of cryptocurrencies presents to SARS and determining whether these problems will also be encountered by tax authorities in Brazil, Russia, India and China (members of the BRICS group of countries). The study examined how the BRICS’ countries were addressing cryptocurrency data challenges and determining whether South Africa could learn from the solutions implemented by these countries. The information gathering powers of SARS were also examined in order to determine whether those powers are on par with those of the BRICS’ countries. The findings suggest that it is vital that tax authorities link the taxpayer’s real identity to the taxpayer’s digital identity in order to trace the taxpayer’s tax profile and verify compliance with tax legislation. The findings also suggest that certain BRICS countries did not experience significant verification difficulties. China has, however, banned the use of cryptocurrencies. Russia is in the process of passing tax legislation pertaining to cryptocurrencies and therefore, the Russian tax authorities have not yet undertaken to verify cryptocurrency transactions. India has addressed the verification challenges presented by cryptocurrencies by introducing legislation that compels clients of cryptocurrency exchanges to register with the exchange before transacting. Brazil is in the process of passing legislation which will require cryptocurrency exchanges to supply the Brazilian tax authorities with taxpayers’ identities, transaction amounts and transaction history on a monthly basis. Private altcoins, face-to-face transactions, cryptocurrency mixers and online peer-to-peer markets (which require no registration) present the largest verification challenges due to the difficulty in tracking these transactions. It was also found that the information gathering powers of SARS are on par with those of the BRICS’ countries and therefore, SARS is also able to request information from cryptocurrency exchanges as a means of collecting data for verification purposes. The study concluded with recommendations for SARS to consider in addressing the verification challenges posed by cryptocurrency transactions.